Associations between smoke-free vehicle legislation and childhood admissions to hospital for asthma in Scotland: an interrupted time-series analysis of whole-population data. (August 2021) - Mackay, Daniel F; Turner, Stephen W; Semple, Sean E; Dick, Smita; Pell, Jill P
Summary: Background: In Scotland, childhood admissions to hospital for asthma fell from March, 2006, after legislation was introduced to prohibit smoking in public places. In December, 2016, new Scottish legislation banned smoking in vehicles containing a child. We aimed to determine whether the introduction of this new legislation produced additional benefits. Methods: We obtained data on all asthma emergency admissions to hospitals in Scotland between 2000 and 2018 for individuals younger than 16 years. We used interrupted time-series analyses to study changes in monthly incidence of asthma emergency admissions to hospital per 100 000 children after the introduction of smoke-free vehicle legislation, taking into account previous smoke-free interventions. We did subgroup analyses according to age and area deprivation, using the Scottish Index of Multiple Deprivation, and repeated the analyses for a control condition, gastroenteritis, and other respiratory conditions. Findings: Of the 32 342 emergency admissions to hospital for asthma among children younger than 16 years over the 19-year study period (Jan 1, 2000, to Dec 31, 2018), 13 954 (43%) were among children younger than 5 years and 18 388 (57%) were among children aged 5–15 years. After the introduction of smoke-free vehicle legislation, there was a non-significant decline in the slope for monthly emergency admissions to hospital for asthma among children younger than 16 years (−1·21%, 95% CI −2·64 to 0·23) relative to the underlying trend in hospital admissions for childhood asthma. However, children younger than 5 years had a significant decline in the slope for monthly asthma admissions (−1·49%, −2·69 to −0·27) over and above the underlying trend among children in this age group (equivalent to six fewer hospitalisations per year), but no such decline was seen in children aged 5–15 years. Monthly admissions to hospital for asthma fell significantly among children living in the most affluent areas (−2·27%, −4·41 to −0·07) but not among those living in the most deprived areas. We found no change in admissions to hospital for gastroenteritis or other respiratory conditions after the introduction of the smoke-free vehicle legislation. Interpretation: Although legislation banning smoking in vehicles did not affect hospital admissions for severe asthma among children overall or in the older age group, this legislation was associated with a reduction in severe asthma exacerbations requiring hospital admission among preschool children, over and above the underlying trend and previous interventions designed to reduce exposure to second-hand smoke. Similar legislation prohibiting smoking in vehicles that contain children should be adopted in other countries. Funding: None.